Water Quality Assessment of Epie Creek in Yenagoa Metropolis, Bayelsa State, Nigeria - , Vivian Nkeiru Ben-Eledo; , Lovet T. Kigigha; , Sylvester C. Izah; , Benjamin O. Eledo (Archives of Current Research International, 2017)
This study evaluated the physicochemical and microbial quality of water samples from Epie creek, Niger Delta. Water samples were collected from five different locations (Akenfa, Agudama-Epie, Tombia, Opolo and Biogbolo) in two seasons viz: dry i.e. January and February and wet season i.e. May and June, 2016). The samples were analyzed following standard procedure. Results from the water quality ranged from 5.80- 7.01 (pH), 0.12 mg/l-2.58 mg/l (salinity), 265.00 -1096.75 µS/cm (conductivity), 31.29-105.04NTU (Turbidity), 133.00-548.50 mg/l (total dissolved solid), 3.74-10.562 mg/l(total suspended solid), 6.23-7.17 mg/l (dissolved oxygen), 65.17-94.95 mg/l (biological oxygen demand), 121.72-252.80 mg/l, (chemical oxygen demand), 6.504-14.30 mg/l (sulphate), 0.63-1.69 mg/l (nitrate), 2.18-4.28 mg/l (Bicarbonate), 15.25-61.75 mg/l (chloride), 19.20-62.00 mg/l (Alkalinity), 52.86-280.00 mg/l (Total hardness), 16.53-43.09 mg/l (calcium), 3.07-10.46 mgl (magnesium), 3.34-16.02 mg/l (sodium), 2.06-5.26 mg/l (potassium), 0.32-2.52 mg/l (iron), 0.016-0.188 mg/l (manganese), Analysis of variance showed that there was significance difference (P<0.05) in most of the location, months and interaction. The values showed that anthropogenic activities (mostly from marketing wastes in the creek is having an impact on the water quality).